The impact of a panel of 18 SNPs on breast cancer risk in women attending a UK familial screening clinic: a case–control study. Issue 2 (28th October 2016) - Evans, D Gareth; Brentnall, Adam; Byers, Helen; Harkness, Elaine; Stavrinos, Paula; Howell, Anthony; ,; Newman, William G; Cuzick, Jack
Abstract : Background: Breast cancer familial risk clinics offer screening and preventive strategies. While BRCA1 / BRCA2 genetic testing provides important risk information for some women, panels of more common breast cancer risk genetic variants may have relevance to greater numbers of women with familial risk. Methods: Three polygenic risk scores (PRS) based on 18 SNPs were investigated in a case–control study of women attending a familial risk clinic. PRS were derived from published general European population allele ORs and frequencies (18-SNPs (SNP18)). In women with BRCA1 / BRCA2 mutations, 3 SNPs/13 SNPs, respectively, generated the PRS estimates. In total, 364 incident breast cancer cases (112 with BRCA1/2 mutations) were matched with 1605 controls (691 BRCA1/2 ) by age last mammogram and BRCA1/2 genetic test result. 87 women with cancer before attendance were also considered. Logistic regression was used to measure PRS performance through ORs per IQR and calibration of the observed to expected (O/E) logarithm relative risk when unadjusted and adjusted for phenotypic risk factors assessed by the Tyrer-Cuzick (TC) model. Results: SNP18 was predictive for non-carriers of BRCA1/2 mutations (IQR OR 1.55, 95% CI 1.29 to 1.87, O/E 96%). Findings were unaffected by adjustment from TC (IQR OR 1.56, 95% CI 1.29 to 1.89) or when prior cancers were included (IQR OR 1.55, 95% CI 1.30 to 1.87). There was some evidence to support polygenic scores with weights for individuals with BRCA1/2 mutations ( BRCA1 IQR OR 1.44, 95% CI 1.17 to 1.76; BRCA2 IQ OR 1.44, 95% CI 0.90 to 2.31). Conclusions: PRS may be used to refine risk assessment for women at increased familial risk who test negative/have low likelihood of BRCA 1 /2 mutations. They may alter the recommended prevention strategy for many women attending family history clinics.